Malawi stories of change in nutrition: Lessons on advocacy - Nowa, Mphatso; Roschnik, Natalie; Chalemera, Jacqueline; Mhango, Brian; Northcote, Callum; Bhaiji, Rashida; Museka Saidi, Tendai (Institute of Development Studies, 2022)
Malawi is one of the most committed countries in Africa to improving nutrition, yet it still has one of the highest rates of malnutrition in the region and is struggling to turn commitments into action at scale. The advocacy component of the Afikepo project strengthened capacity of national and district government and Civil Society Organisation (CSO) representatives to plan, budget and advocate for scaling up nutrition commitments at national and in 10 districts. These actions improved awareness, coordination and commitment to prioritise nutrition across sectors, within government, and CSOs and a wide range of actors at national and district level, which in turn improved governance and accountability. However, these actions did not have a substantial effect on domestic funding allocations, which are still heavily reliant on external donors. This brief summarises lessons learned and recommendations from the various advocacy and capacity building efforts over the past four years.